The Mediating Effect of Blood Pressure on Budget Allocation and Audit Quality Relationship: An Experimental Investigation - Rohma, Frida Fanani; Shofiyah, Indah; Fitriyah, Anik (IAPI, 2025)
This study investigates the mediation effects of blood pressure on budget allocation and audit quality relationships. Not being able to ignore the allocation guide that contains time, resources, and cost allocation during the auditing process can cause stress. It can reduce the physiological (e.g., blood pressure) as well as the cognitive abilities that reduce performance. This research uses social laboratory experiments. Budget allocation manipulates into three conditions (specified, partial, and unspecified). Blood pressure was categorized into three levels (high, normal, and low), and audit quality was measured during the experiment. The result of two regression model equations shows that budget allocation influences blood pressure, and a correlation between blood pressure and audit quality was found. This research employed a construal-level perspective and found that blood pressure partially mediates budget allocation on audit quality relationships. The existence of budget allocation increases low-level construal and becomes a trigger that affects blood pressure; changes in blood pressure from normal levels indicate the condition of the circulation of blood pressure in the way of blood supply to the brain is not optimal, thus affecting the individual abilities, and audit quality.